Criminology Review on Narcotics Abuse by Students in Pontianak - Klara Dawi; Hendrik Hendrik; AS Yenny (Proceedings of AICS - Social Sciences, 2018)
Circulation and abuse of narcotics today is not only faced by Indonesia, but also a problem for all countries in the world. As a country in cross-world position, Indonesia  threatened by the danger of narcotics is very high, and then one of the provinces in Indonesia directly adjacent to the state of Malaysia namely West Kalimantan Province with the Provincial Capital located in Pontianak is also threatened by the danger of circulation and abuse narcotics. According to data obtained from the National Narcotics Agency of Pontianak, within 3 years (2014-2016), the students were exposed to the use of narcotics cases amounting to 54 people, which is in general they used the narcotics along with their friends. Based on this condition, the government through the police department and the narcotics agency to make prevention efforts through the provision of information about the dangers of narcotics abuse, as well as the raids on the place of entertainment as well as the rented house and boarding house.Keywords:narcotics abuse, students.